I spy : shapes in art - Micklethwait, Lucy. (London : Harper Colins Children's Books, 2004)
Presents objects with the shape of a heart, a triangle, a square and other shapes through paintings by such artists as Magritte, Escher, and Matisse.
Keywords: Art appreciation; Geometry in art; Shape; Size